2013
DOI: 10.1051/epjconf/20135904004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mix experiments on Omega

Abstract: Abstract.A 2-D Eulerian code with a turbulent mix model was used for the first time to model a set of plastic (CH) ablator capsules with 15 m thick CH shells. Our simulations of these capsules do a reasonable job of matching the implosion radius versus time, self-emitting core radius, and have an experiment/simulation yield ratio that is about 0.24.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…The bang times of the day 2 capsules are about 100 ps later, just as was seen for the exploding pusher capsules earlier. Those results are described in more detail below and in Bradley et al 21 Thick shell perfect capsule simulations show trends similar to those found for the thin perfect capsules. The YOM values are 0.25 to 0.28, simulated T ion values are 2.6 keV higher than the data (see Fig.…”
Section: Thick Capsulessupporting
confidence: 76%
See 2 more Smart Citations
“…The bang times of the day 2 capsules are about 100 ps later, just as was seen for the exploding pusher capsules earlier. Those results are described in more detail below and in Bradley et al 21 Thick shell perfect capsule simulations show trends similar to those found for the thin perfect capsules. The YOM values are 0.25 to 0.28, simulated T ion values are 2.6 keV higher than the data (see Fig.…”
Section: Thick Capsulessupporting
confidence: 76%
“…The average difference between the experimental and the simulated radii in a radius versus time plot is 19 lm. 21 This validates the energy sourcing prescription used in place of the absent laser propagation and absorption physics.…”
Section: -5supporting
confidence: 68%
See 1 more Smart Citation